Levosimendan for Pediatric Anomalous Left Coronary Artery From the Pulmonary Artery Undergoing Repair: A Single-Center Experience - Wang, Chunrong; Gong, Junsong; Shi, Sheng; Wang, Jianhui; Gao, Yuchen; Wang, Sudena; Peng, Yong G.; Song, Jing; Wang, Yuefu (Frontiers in Pediatrics, 2018)
Objectives: Our aim was to retrospectively evaluate the benefit of levosimendan in certain complicated congenital heart procedures such as the pediatric anomalous origin of the left coronary artery from the pulmonary artery (ALCAPA) with moderate or severe cardiac dysfunction and its repair. Study Design: We enrolled 40 pediatric patients with ALCAPA and moderate or severe left ventricular dysfunction. Patients who had a preoperative left ventricular ejection fraction (LVEF) of 50% or less and had undergone the surgical correction of their coronary artery through cardiopulmonary bypass met the criteria of our study. Twenty patients were given 0.1-0.2 µg/kg/min levosimendan at the induction of anesthesia, which lasted for 24 hours. The remaining 20 patients were not given levosimendan. Results: The mean preoperative LVEF in the levosimendan group was significantly lower than that in the non-levosimendan group (22.5%  10.7% vs 31.8%  8.1%, p = 0.004). On postoperative day 7, the LVEF in the levosimendan group was still significantly lower (27.1%  8.9% vs 37.5%  11.0%, p = 0.002). There was no significant difference in LVEF detected on day 7 [median 30.8%, interquartile range (IQR) −4.4% to 63.5% vs median 15.1%, IQR −3.5% to 40.0%, p = 0.560)] or at follow-up of about 180 days (median 123.5%, IQR 56.1%−222.6% vs median 80.0%, IQR 36.4%−131.3%, p = 0.064). There was no significant difference between the two groups in postoperative vasoactive-inotropic score (VIS) at any of the time points of 1, 6, 12, 24, and 48 hours (p = 0.093). Three patients had to be supported by extracorporeal membrane oxygenation when difficulty appeared in weaning off cardiopulmonary bypass because of low cardiac output in the non-levosimendan group, but no patient needed extracorporeal membrane oxygenation after levosimendan infusion (p = 0.231). The length of intensive care unit stay (median 10.5 days, IQR 7.3−39.3 days vs median 4.0 days, IQR 2.0−10.0 days, p = 0.002) and duration of mechanical ventilation (median 146.0 hours, IQR 76.5−888.0 hours vs median 27.0 hours, IQR 11.0−75.0 hours, p = 0.002) were revealed to be longer in the levosimendan group.